1995
DOI: 10.1145/223427.211856
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion and reuse in an object-oriented system

Abstract: We define and apply two new measures of object-oriented class cohesion to a reasonably large C++ system. We find that most of the classes are quite cohesive, but that the classes that are reused more frequently via inheritance exhibit clearly lower cohesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
1
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 4 publications
0
95
1
5
Order By: Relevance
“…An assortment of realized quantities and qualitative ordinal scales have been defined for cohesion and coupling [50,51,52].…”
Section: Architecture or Design As Objectmentioning
confidence: 99%
“…An assortment of realized quantities and qualitative ordinal scales have been defined for cohesion and coupling [50,51,52].…”
Section: Architecture or Design As Objectmentioning
confidence: 99%
“…If there is only one set in a class, COR will result in 1, which indicates a high cohesion. Ferreira et al (2011) carried out an experimental evaluation of four cohesion metrics: LCOM (lack of cohesion in methods) (Chidamber and Kemerer 1994), LCOM4 (Hitz and Montazeri 1995), TCC (tight class cohesion) (Bieman and Kang 1995), and COR. Findings of that work showed that COR may be used as a good indicator of class cohesion and it is useful in identifying classes with design deviance.…”
Section: A Metric For βmentioning
confidence: 99%
“…Existing techniques can measure cohesion from different levels of the source code. In the context of our study, we use techniques to measure cohesion in classes (5,39) and are explained in detail in Section 3.5.…”
Section: Internal Quality Attributesmentioning
confidence: 99%
“…After, we investigated the quality metrics for quantifying each internal quality attribute. We defined a set composed by 25 quality metrics based on previous work (6,30,31,39,42,45,46). To select appropriate metrics per internal quality attribute, we applied the following criteria.…”
Section: Measuring Internal Quality Attributesmentioning
confidence: 99%
See 1 more Smart Citation